Co-culture of Murine Neurons Using a Microfluidic Device for The Study of Tau Misfolding Propagation - Grace Hallinan; Dianne Lopez; Mariana Vargas-Caballero; Jonathan West; Katrin Deinhardt (Bio-Protocol, 2020)
The deposition of misfolded, aggregated tau protein is a hallmark of several neurodegenerative diseases, collectively termed “tauopathies”. Tau pathology spreads throughout the brain along connected pathways in a prion-like manner. The process of tau pathology propagation across circuits is a focus of intense research and has been investigated in vivo in human post-mortem brain and in mouse models of the diseases, in vitro in diverse cellular systems including primary neurons, and in cell free assays using purified recombinant tau protein. Here we describe a protocol that takes advantage of a minimalistic neuronal circuit arrayed within a microfluidic device to follow the propagation of tau misfolding from a presynaptic to a postsynaptic neuron. This assay allows high-resolution imaging as well as individual manipulation of the releasing and receiving neuron, and is therefore beneficial for investigating the propagation of tau and other misfolded proteins in vitro.